Prevalence of G6PD deficiency in neonates and verification of cord blood reference range using OSMMR2000-D – a tertiary hospital experience - A Talib, Noorlelawati; Abdul Halim, Sarah; Nasiruddin, Dhamirah (Malaysian Society of Pathologists, 2023)
Introduction: Glucose-6-phosphate-dehydrogenase (G6PD) produces nicotinamide-adenine-dinucleotide-phosphate (NADPH), which protects against oxidative stress. The prevalence of G6PD deficiency in Malaysia is 3.4%. Our centre has opted for quantitative G6PD assay to overcome the disadvantages of the national screening method, the fluorescent spot test (FST). This study aims to verify the reference range for cord blood using OSMMR2000-D G6PD Assay, establish the prevalence of G6PD deficiency in our local population and compare the G6PD activity of female and male neonates. Methodology: This was a retrospective cross-sectional study involving 666 cord blood samples sent over a four-month period to the Haematology Laboratory of Sultan Ahmad Shah Medical Centre (SASMEC @IIUM) Kuantan for G6PD assay. The samples were assayed using OSMMR2000-D G6PD Assay. Verification of the reference range was done by analysing twenty random specimens. G6PD activities of each sample were recorded and analysed using the statistical package programme (SPSS) version 28.0. Results: This study population comprised 320 (48%) female and 346 (52%) male neonates. Most of the neonates were Malay (88.4%), followed by Chinese (8.4%), Indian (1.1%) and others such as Arab (2.1%). The reference range was verified as out of the twenty samples, no more than 2 samples fell outside the normal reported limit, hence the reference range was valid. The mean G6PD activity overall was 12.062 U/gHb. The mean G6PD activity for female neonates was 12.213 U/ gHb, whilst for male neonates was 11.921 U/gHb. There was no significant difference between male and female neonates (p>0.05). The overall prevalence of G6PD deficiency when assayed using OSMMR2000-D is 3.9%. Discussion: This study has verified the reference range for our centre and confirms that G6PD prevalence in our local population is comparable to national prevalence. There is no significant difference between the mean G6PD activity of male and female neonates, indicating that no gender-adjusted reference range is necessary.